Evaluation of COLIA1 gene rs1107946 polymorphism in relation to bone mineral density and fracture risk in Slovak postmenopausal women - Boroňová, Iveta; Mathia, Matúš; Mačeková, Soňa; Bernasovská, Jarmila; Gaľová, Jana (Central European journal of public health, 2023)
OBJECTIVES: The aim of the study was the evaluation of the rs1107946 polymorphism of the COLIA1 gene impact on bone mineral density and fracture risk in Slovak postmenopausal women. METHODS: One hundred and twenty-seven postmenopausal Slovak women with a diagnosis of osteopenia/osteoporosis were genotyped for rs1107946 polymorphism of the COLIA1 gene. Clinical and anthropometric data were obtained. DNA isolation was performed using a standard protocol. Genetic analyses of the rs1107946 polymorphism of the COLIA1 gene were performed by the TaqMan SNP genotyping assays. RESULTS: The study confirmed a statistically significant relationship using an association analysis between the rs1107946 polymorphism of the COLIA1 gene genotypes and body weight of the Slovak postmenopausal women with osteopenia/osteoporosis (p = 0.03). The study revealed a significant association of the risk T allele of the rs1107946 polymorphism of the COLIA1 gene with osteoporotic fractures (p = 0.038). The odds ratio confirmed 2.060 times higher risk of osteoporotic fractures in Slovak postmenopausal women with the presence of risk T allele of the rs1107946 COLIA1 gene polymorphism (OR = 2.060; 95% CI: 1.024-4.144). CONCLUSION: The results of this study revealed an association of T allele of the rs1107946 COLIA1 gene polymorphism with osteoporotic fractures in Slovak postmenopausal women with osteopenia/osteoporosis and suggest that the rs1107946 polymorphism of the COLIA1 gene may be a molecular biomarker usable in the management of osteoporosis.
Keywords: Osteoporosis, Postmenopausal; Slovakia; Slovenská republika; Genotype; polymorfismus genetický; osteoporosis; postmenopauza; Osteoporosis; osteoporóza; Polymorphism, Genetic; postmenopauzální osteoporóza; Postmenopause; lidé; ženské pohlaví; Humans; kostní denzita; Bone Density; osteoporotické fraktury; genotyp; fracture risk; postmenopausal women; Female; COLIA1 gene - rs1107946 polymorphism; Osteoporotic Fractures